PROGRAM INOVASI GERAKAN “BERINISIATIF (BERIKAN HANYA ASI EKSKLUSIF)” SEBAGAI UPAYA MEWUJUDKAN GENERASI EMAS BERKUALITAS - Brivian Florentis Yustanta; Dintya Ivantarina (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
All the essential nutrients required for survival, growth, development and immunological, antimicrobial, and anti-inflammatory factors in infants are obtained from breast milk during the first six months of life. However, the problem of not achieving exclusive breastfeeding coverage is still a major problem in infants beside the increase in infant mortality in the first six months of life. This is also a problem at the Mojoagung Health Center, especially in Dukuhdimoro village regarding the achievement of exclusive breastfeeding coverage from January - March 2022 which still does not meet the target of (-) 16.79%. This is due to the lack of knowledge of mothers since pregnancy and socialization from health cadres about exclusive breastfeeding. These problems require community service activities in the form of an innovation program in the form of the "Berinisiatif (Give Only Exclusive Breastfeeding)" movement through education and socialization of exclusive breastfeeding as an effort to create a quality golden generation. The activity will be carried out from June 20 to 30, 2022 starting from the planning stage to the evaluation stage. The number of participants was 30 consisting of pregnant and lactating women and health cadres in Dukuhdimoro Village, Mojoagung District, Jombang Regency. The implementation method was in the form of education and socialization about exclusive breastfeeding with lectures, questions and answers, and discussions. The evaluation used pretest and posttest questionnaires. The results of providing education showed an increase in participants regarding exclusive breastfeeding compared to before being given education. After providing education to the participants, it was continued with the socialization activity of the “Berinisiatif” movement. The results of the socialization of this program later that pregnant and lactating mothers as the main actors in exclusive breastfeeding can succeed in the government's program in realizing a quality golden generation through optimizing nutritional needs in the first 1000 days of an infant's life.